Slovakia: Taxation Policy in the Light of EU Tax Policy - Vartašová, Anna (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter presents a broad overview of the dynamics of the coexistence of a Member State – the Slovak Republic – and the European Union (EU), which share competencies in the area of taxation. From the perspective of the Slovak Republic, this chapter examines the general concept of state sovereignty; further, it explores how the Slovak Republic’s sovereignty is affected by its membership in the EU, especially in light of new tax legislation. Conferring part of its sovereignty to the EU, the Slovak Republic applies the monistic principle of regulating the relationship between EU law and national law and prioritizes EU law over its own. Notably, this chapter also explores the EU’s direct legislative competences in tax matters and its visions and efforts in the sphere of direct taxation, where its legislative position differs from that for indirect taxes. In this regard, Slovakia can be seen as a supporter of EU legislative actions that lead to a more cooperative approach towards common European problems; however, not all initiatives were perceived as beneficial for the Slovak Republic – some may hold risks for the state’s economy. Given that a Member State’s sovereignty and tax competence are closely connected to tax competition, this chapter also considers this topic; in particular, this chapter explores why Slovakia did not positively receive some of the EU’s proposals, particularly the Common Consolidated Corporate Tax Base (CCCTB). Subsequently, this chapter turns to the Slovak Republic’s overall policy and particular measures in the fight against tax evasion in light of its attitude towards EU. This area is of special importance for the Slovak Republic. In the last decade, the Slovak Republic has introduced action plans for fighting tax evasion and tax fraud and many related individual measures. Further, Slovakia generally affirms the EU’s related measures as helpful in solving tax evasion. The data show that these activities are yielding positive outcomes in Slovakia, with the amount of taxes evaded generally declining.Keywords: Slovakia, tax law, tax sovereignty, tax harmonisation, implementation of EU measures, tax competition, fighting tax avoidance